Det kgl. Landhusholdningsselskabs Generalforsamling den 15de December 1875. - la Cour, J. C. (Tidsskrift for Landøkonomi, 2018)
Det kgl. Landhusholdningsselskabs Generalforsamling den 15de December 1875.